International Legal Issues in the Conservation of Marine Genetic Resources - P. V. Sotskova (Московский журнал международного права, 2024)
INTRODUCTION. Nowadays the issues concerning conservation of marine biological diversity become important for the community of States in the light of the expansion of the scale of economic activity in marine spaces and of the opportunities of using such resources. At the universal contractual level an answer was proposed to a number of questions that have arisen in this area: on March 4, 2023, the text of the Agreement (under the 1982 United Nations Convention on the Law of the Sea) with a long title: “on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction” was ﬁnalized. It is predicted that the entry into force of this Agreement in the future will create a multilateral legal basis for conservation of biological diversity on the high seas, with the orderly use of its biological resources, to protect such diversity based on the principle of cooperation between States.The purpose of the article is to analyze the legal regime of marine genetic resources conservation based on the text of this Agreement.MATERIALS AND METHODS. The subject of this study comprises international treaties, international customs, general principles of international law and other sources of international law related to conservation of marine biodiversity in general. The methodological basis of the research is represented by a wide range of research methods, namely: formal-legal, comparative-legal, historical-legal and system-structural methods. In addition, the author applied the methods of analysis and generalization.RESEARCH RESULTS. The article presents a comprehensive analysis of the international legal regime of marine genetic resources based on the provisions of the Agreement under the United Nations Convention on the Law of the Sea on the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction. The author considers the history of the development of the draﬅ Agreement, analyzes its main provisions, and pays special attention to its innovative legal mechanisms.The author proposes their assessment of the content of the draﬅ Agreement as a universal legal basis for the conservation of marine biological diversity, and suggests some options for strengthening international cooperation in this area.DISCUSSION AND CONCLUSIONS. As a result of the study, it can be stated that the draﬅ Agreement, prepared over many years of negotiations and published in March 2023, is a signiﬁcant political and legal achievement of a universal level in the ﬁeld of marine biodiversity conservation. At the same time, one can not fail to note the rather general nature of this document, as well as the fact that the entry into force of the Agreement may also require considerable time: objectively, the interests of developed and developing countries in this area are not always close; moreover, each State party to the Agreement accepts the obligation, among other things, that the use of marine natural resources should be linked to the obligation to protect marine environment, and this is always sensitive: a number of developed countries, as is known, under the pretext of economic concern, impose on developing States “green” products of their enterprises, which exacerbates the gap between developed and developing States.That is why the author comes to the conclusion that the international community, along with the development of a universal international treaty, could take the path of developing regional agreements to clarify such a legal regime, which would also contribute to the strengthening of the legal regime for biodiversity conservation at the universal level.